Análisis económico de la fertilización en fríjol en el Norte del Cauca (1989)
This paper had as objective the agroeconomic evaluation at farm level of various national phosphorus products, comparing them with complete and organic fertilizers in products dosages suggested by farmers. It was based on the physical results obtained by the International Fertilizer Development Center Phosphorus Proyect, and the Colombian Agricultural Institute (LC.A.) in the technology District of "Santander de Quilichao" in Caldono, in soils of clay loam texture, acid pH, and physical and chemical homogeneous characteristics. Two experiments were analyzed; the first one was directed to study the behavior of colombian phosphorus products at farm level with non grouped and grouped data, based on four groups of farms, classified according soil characteristics and management. In the second experiment the fertilization response of mixtures suggested by farmer was studied. Economic analysis of the first experiment showed for both kind of data that hen dung was the best treatment, because it presented the highest benefits and was the least risky for the farmer. The second best treatment was 35-30-30 of P, N and K20, respectively. In mixtures suggested by farmers, the best treatment was 267 kg/ha of 10-30-10 of N, P and K plus 900 kg/ha of phosphate rock.